Pengaruh Disiplin Kerja dan Pengawasan Terhadap Kinerja Pegawai di Kantor Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Kabupaten Ngada, Provinsi Nusa Tenggara Timur - Jawa, Silvester; Djani, William; Suratinah, Suratinah (Universitas Ekasakti, 2024)
In organizing personnel services at the Office of the Ngada Regency Personnel and Human Resources Development Agency (BKPSDM), the main obstacle faced is the lack of application of work discipline and supervision within the Ngada Regency BKPSDM Office. The objectives of this writing include: to determine how much influence work discipline has on the performance of employees of the Ngada Regency BKPSDM office, to determine how much influence supervision has on the performance of employees of the Ngada Regency BKPSDM office, and to determine how much influence work discipline and supervision have on the performance of employees of the Ngada Regency BKPSDM office. This research was conducted at the Office of the Ngada Regency Personnel and Human Resources Development Agency (BKPSDM), with a population of 36 people using the census method, namely all the population was sampled. The independent variables in this study are work discipline and supervision while the dependent variable is employee performance. Measurement of variables in this study using a Likert scale and SKP BKPSDM Kab. Ngada employees. Data processing with a statistical approach of multiple regression analysis using SPSS 22. From the standard estimated for the variables of Work Discipline (X1), Supervision (X2), Employee Performance (Y), the structural equation can be made as follows Y = 368.232 + 0.544 + 2.224. the results of data analysis show that work discipline has a significant effect on employee performance within the BKPSDM of Ngada Regency with a coefficient of determination of 31.2%, Supervision has an effect of 37.1% on performance, and Work discipline and Supervision have an effect of 39% on performance and the rest is influenced by other factors not examined.